Short-term and long-term alterations of gastrointestinal microbiota with different H. pylori eradication regimens: A meta-analysis - Chen, Bing; Li, Xin-meng; Cai, Ting; Wang, Fen (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aims: The impacts of Helicobacter pylori (H. pylori) eradication on the gastrointestinal microbiota are controversial, and whether the short-term and long-term changes in the gastrointestinal microbiota following different eradication regimens are consistent remains inconclusive. This study aimed to examine the effects of various eradication regimens on the gastrointestinal microflora at follow-up evaluations within 7 days, at 1-3 months, and over 6 months changes in the gastrointestinal microbiota. Materials and Methods: Studies reported on the PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrails.gov databases before March 2022 were collected. Data analysis and visualization were conducted using Review Manager 5.4.1. The tool of the Cochrane Collaboration to assess the risk of bias was suitable for randomized controlled trials with the Newcastle–Ottawa scale for nonrandomized controlled trials. In addition, the process was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: After a series of rigorous screenings, a total of 34 articles with 1,204 participants were included for this review analysis. The results showed changes in the gut microflora at the phylum level or the family and genus levels. After metronidazole-containing triple therapy, the number of Enterobacteriaceae increased at 1-3 months follow-up. After Metronidazole-free triple therapy, Actinobacteria decreased significantly, and this trend lasted for more than 6 months. Within 7 days after eradication treatment, the follow-up results showed a decrease in the number of Lactobacillus. After Bismuth-containing quadruple therapy, the changes in Actinobacteria fluctuated with the follow-up time. The changes in Proteobacteria showed a downward trend lasting for 1-3 months after eradication but returned to baseline levels over 6 months after eradication. Subgroup analyses indicated that host age could influence changes in the gut microbiota. Conclusion: Different eradication regimens had varied effects on the short-term and long-term abundance of the gastrointestinal microbiota, but the decreasing trend of the microbiota diversity was the same for all regimens at the short-term follow-up. This study summarizes the changes of gut microbiota at different stages after different eradication regimens and hope to provide some references for supplementing probiotics, while further studies is needed to support these findings.